2010
DOI: 10.3109/17453674.2010.519164
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb amputations in Trondheim, Norway

Abstract: Background and purposeIn the city of Trondheim, Norway, diabetic lower-limb amputations accounted for one-third of all lower-limb amputations (LLAs). In an attempt to reduce this rate, a diabetic foot team was established in 1996. We present the incidence of LLA in Trondheim as measured 10 years later.Patients and methodsIn 2004–07, we registered all LLAs performed in Trondheim and then compared the data with previously published data from 1994–1997. From 1996 through 2006, we registered the activity of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
7
34
0
Order By: Relevance
“…While there are others who report no change in amputation rates, 14,15 most research supports an overall trend toward a significantly declining incidence. [3][4][5][6][7][8][9] Reasons for unchanged amputation incidence rates must be carefully considered in order to build effective care strategies. It was expected that there would be a shift toward an older age for people undergoing their first amputation as more interventions aim to prevent or delay the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are others who report no change in amputation rates, 14,15 most research supports an overall trend toward a significantly declining incidence. [3][4][5][6][7][8][9] Reasons for unchanged amputation incidence rates must be carefully considered in order to build effective care strategies. It was expected that there would be a shift toward an older age for people undergoing their first amputation as more interventions aim to prevent or delay the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Most studies focus on amputations in people with diabetes. 1 For the Netherlands, a reduction from 550 to 363 amputations per 100,000 people with diabetes was reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is deemed to enable a more systematic treatment of diabetic foot ulcers, a shorter period of healing, and fewer amputations resulting from foot ulcers (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 Studies from different European countries were able to show a statistically significant decrease in the incidence of diabetes-associated amputations over the last decade. [8][9][10][11] It was observed that this was the result of a significant reduction in major amputation rates with a growing incidence of minor amputations. 12 Most available studies focused on the prevention of amputation and did not investigate the long-term prognosis and survival of patients.…”
Section: Introductionmentioning
confidence: 99%